PERBAIKAN KONTRAS CITRA MENGGUNAKAN TEKNIK BRIGHTNESS ADJUSTMENT UNTUK SISTEM EKSTRAKSI GARIS PANTAI - Rai Putera Yasa, I Made; Oka Widyantara, I Made; Wirastuti, NMAE Dewi (Jurnal SPEKTRUM, 2018)
This study has evaluated the application of brightness adjustment technique to improve image contrast in the framework of coastline extraction on video-based shoreline monitoring system. In this monitoring system, the shoreline detection mechanism is done by introducing the land and sea objects in the video image. Changes in sea conditions due to weather changes cause a change in the contrast in the coastal image. The change in contrast will lead to inaccurate coastline detection. The brightness adjustment technique is applied to the image pre-processing to produce stable contrast in all conditions so that the coastal monitoring system can extract the coastline accurately. The brightness adjustment technique can adjust the brightness of the coastal image by setting the upper and lower threshold values of each pixel intensity. This study used 3 (three) sample video test images taken on morning, noon and afternoon to obtain different video image characteristics. The simulation results show that the application of brightness adjustment technique can increase the accuracy of shoreline extraction when using the threshold value of each at -20% for morning image condition, -40% for daytime image condition, and -35% for afternoon image condition .